Two live sightings of Sowerby's beaked whale (Mesoplodon bidens) from the western Mediterranean (Tyrrhenian Sea). (23rd January 2017) - Bittau, Luca; Leone, Mattia; Gannier, Adrien; Gannier, Alexandre; Manconi, Renata
Abstract : Sowerby's beaked whale ( Mesoplodon bidens ) was previously known in the Mediterranean Sea from a single live stranding of two individuals in the French Riviera. We report here on two live sightings in the western Mediterranean, central-western Tyrrhenian Sea off eastern Corsica (Montecristo Trough) and off eastern Sardinia (Caprera Canyon) in 2010 and 2012, respectively. In both cases single individuals, possibly the same individual, occurred within groups of Cuvier's beaked whales ( Ziphius cavirostris ) suggesting inter-specific interactions. Based on our close observations of mixed-species groups of Sowerby's and Cuvier's beaked whales, we hypothesize that some previous long-distance sightings of beaked whales in the Mediterranean may not be reliably attributed to Z. cavirostris . The present sightings and previous live stranding indicate that the western Mediterranean Sea is the easternmost marginal area of M. bidens within the North Atlantic geographic range. Notes on behaviour are also provided.